Noise and the risk of tinnitus: A two‐sample Mendelian randomized study - He‐Sen Huang; Kai‐Qin Chen; Wen‐Kao Zhou; Bin Zhang; Jing Gao; Fei Xie; Yu Du (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objectives Observational studies imply that noise may increase the likelihood of developing tinnitus. However, no causal relationship has been established between the two using Mendelian randomization (MR) analysis, we aimed to determine the potential causal relationship between noise and various categories of tinnitus. Methods We extracted single nucleotide polymorphisms (SNPs) associated with noise and tinnitus from a large genome‐wide association study (GWAS) of European individuals. UK Biobank (UKB) provided summary data for both entities. Inverse variance weighting (IVW) was implemented as the primary method for evaluating effect estimates. Using Weighted median and MR–Egger regression, heterogeneity and pleiotropy were evaluated using sensitivity analyses. Results The random‐effects IVW approach revealed a causal relationship between noise and the three onset tinnitus (odds ratio [OR] = 1.052, 95% confidence interval [CI] = 1.013–1.092, p = 0.008; OR = 1.248, 95% CI = 1.177–1.323, p = 0.001; OR = 1.133, 95% CI = 1.058–1.213, p = 0.001). Noise was not a risk factor for tinnitus in the past (OR = 0.999, 95% CI = 0.934–1.068, p = 0.969). Validation with various Mendelian randomization methodologies and sensitivity analyses confirmed the findings' consistency. Conclusion This Mendelian Randomization study provides causal evidence that noise is a risk factor for the onset of tinnitus but is not a risk factor for developing tinnitus in the past.